1993
DOI: 10.1002/apmc.1993.052120101
|View full text |Cite
|
Sign up to set email alerts
|

Poly(phthalidylidene arylene)s: Synthesis of poly(3,3‐phthalidylidene‐4,4′‐biphenylylene) by precipitative homopolycondensation of 3‐(4‐biphenylyl)‐3‐chlorophthalide

Abstract: The synthesis of poly(3,3-phthalidylidene-4,4' -biphenylylene) (PPB) by precipitative Friedel-Crafts homopolycondensation of 3-(4-biphenylyl)-3-chlorophthalide was studied. The polymer-catalyst complex precipitated from the initially homogeneous reaction mixture was shown to be active and providing the growth of macromolecular chains. The polymer obtained in the form of smooth, transparent glass-like particles, depending on the reaction parameters, may have either uni-or bimodal molecular weight distribution. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…after phase separation. Recently we have [6][7][8][9][10] shown that precipitation electrophilic Friedel Crafts polycondensation can be performed in such a way that the polymer precipitate presents quite uniform small particles. This process has unquestionable technological advantages, since pure polymer can be recovered just by filtration followed by washing with organic solvents and drying.…”
Section: Introductionmentioning
confidence: 99%
“…after phase separation. Recently we have [6][7][8][9][10] shown that precipitation electrophilic Friedel Crafts polycondensation can be performed in such a way that the polymer precipitate presents quite uniform small particles. This process has unquestionable technological advantages, since pure polymer can be recovered just by filtration followed by washing with organic solvents and drying.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Br-TEG presents no acute toxicity compared to methyl iodide, which we previously used in the nucleophilic substitution reaction with the alcohol group. 25 1 H, 13 C NMR, and LC-MS confirmed the successful formation of the AA monomer (Fig. 2B and Table S1, Fig.…”
Section: Monomer Synthesismentioning
confidence: 62%
“…S1, ESI †). 13 63 mmol, 1 eq.,) was dissolved in anhydrous DMF (120 mL) under an inert atmosphere. 2-[2-(2-methoxyethoxy)ethoxy]ethyl bromide (Br-TEG) (7.92 mL, 31.99 mmol, 1.63 eq.)…”
Section: Monomer Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…It seems very likely that the rearrangement proposed represents a consequence of cation transformations resulting in formation of more stable ions (e.g. 8). From this point of view, analysis of the results of polymer preparations using different monomers and different reaction conditions may contribute to clarify the rearrangement mechanism.…”
Section: Resultsmentioning
confidence: 99%